Neural Correlates of Healthy Sustained Vowel Phonation Tasks: A Systematic Review and Meta-Analysis of Neuroimaging Studies. - Dedry, Marie; Maryn, Youri; Szmalec, Arnaud; Lith-Bijl, Julie van; Dricot, Laurence; Desuter, Gauthier (Journal of Voice, 2024)
This review of the methodology and results of studies involving a sustained vowel phonation task during functional Magnetic Resonance Imaging (fMRI) aims to contribute to the identification of brain regions involved in phonation for healthy subjects. This review was performed using the PubMed electronic database. A review was conducted, according to PRISMA guidelines, between September and November 2020, using the following search term pairs: "fMRI and Phonation" and "fMRI and Voice." Activation likelihood estimation analysis was performed. A qualitative analysis was also performed to specify the frequency of activation of each region, as well as the various activation clusters within a single region. Seven studies were included and analyzed. Five of the seven studies were selected for the activation likelihood estimation meta-analysis which revealed significant convergent activation for only one cluster located in the left precentral gyrus (BA4). A qualitative review provides an overview of brain activation. Primary motor and premotor areas were the only activated areas in all studies included. Other regions previously considered to be implicated in phonation were often activated in sustained vowel phonation tasks. Additionally, areas generally associated with articulation or language also showed activation. Methodological recommendations are suggested to isolate the phonatory component and reduce variability between future studies. Based on the qualitative analysis, this review does not support a distinction between regions more related to phonation and regions more related to articulation. Further research is required seeking to isolate the vocal component and to improve insight into human brain network involved in phonation.